Economic evaluation of tilapia production in cages in the middle Paranapanema-SP - Costa, Jesaias Ismael da [UNESP]; Sabbag, Omar Jorge [UNESP]; Martins, Maria Inez Espagnoli Geraldo [UNESP] (My University, 2018)
The tilapia is an agricultural activity that due to its expansion, increasingly needs economic information to demonstrate its viability. This study aimed to evaluate the profitability of farming of tilapia in the middle Paranamema-SP-Brazil. Fish farms were selected from different sizes (small, middle and large) and, through a questionnaire, were obtained information about growth performance, expenses, infrastructure and sales channel, which were used to calculate the cost of production and indicators profitability. All projects proved profitable, the cages and the feed were the most expensive item in initial investment and cost of production, respectively. The sales price and the destination of the production were the main responsible for the variation in the enterprises profitability.
Keywords: Fish farm; Production cost; Profitability